Menstrual phase and symptoms affect match running for elite football players - Brown, G.; Duffield, R. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Menstrual cycle phases are reported to affect athletic performance, though research related to football match running remains inconclusive1. Further, the influence of menstrual symptoms (e.g., stomach cramps) on athletic performance has received increasing attention2,3, though research in football is also scarce. Given a variety of studies report 24-100% of professional footballers perceive negative effects of the menstrual cycle on match performance4,5, further research is required. Therefore, this study aimed to examine whether menstrual cycle phase (menstruation [MP], late follicular [FP], luteal [LP]) and symptoms affect running performance during professional matches. METHODS: Twenty-one naturally cycling football players from 4 professional teams were monitored for up to 4 menstrual cycles during the 2022/23 season. Menstrual status and phase were determined by self-reporting of menstruation and two urinary hormone tests, including luteinizing hormone and pregnanediol (urine progesterone metabolite), respectively. Menstrual phase was classified as MP, FP and LP. On match day evenings players reported menstrual symptom severity from an 18-item questionnaire. Players wore GPS each match and GPS measures (total distance, high-speed running distance, sprinting distance, acceleration count, deceleration count, peak speed) were expressed relative to minutes played. Linear mixed models were performed for each GPS measure with menstrual phase or symptoms as the fixed effect, player ID nested in team as a random effect and position as a random effect. RESULTS: Data for 7 players was included for analysis, resulting in 54-57 observations per model. A significantly higher total distance and was reported during the FP compared to MP (p=0.04) and LP (p=0.007). Significantly greater high-speed running was reported during the FP compared to MP (p=0.012) and LP (p=0.007). No significant effect of menstrual phase was found for sprinting, accelerations, decelerations or peak speed (p>0.05). Accelerations declined with increasing overall menstrual symptom severity (p=0.021). Accelerations also declined with increasing severity of cravings (p=0.03), bloating (p=0.025), lower back pain (p=0.011), joint pain (p=0.023), dizziness (p=0.03) and nausea (p=0.016). Menstrual symptom severity did not affect any other GPS measures (p>0.05). CONCLUSION: Our study is novel in exploring menstrual phase and symptom effects on match running in football. Total and high-speed running distances were greatest during the FP, though large variability existed between and within players, suggesting an individualised approach is still required. Menstrual symptoms can also affect match running, thus management of symptoms may reduce the negative impact on performance.